Written Speech Differential Diagnostics of Primary School Children With Speech Deviance - Alekseeva, E (KnE Life Sciences, 2018)
Modern logopaedic examination schemes do not sufficiently reveal the psychological and pedagogical status of primary school children with speech disorder to work out an individual correction route. The question of children condition with writing disorder of psychological level of its organization is not fully studied. The topical question in logopaedics is still the development of a written speech survey, considering the neuropsychological approach. We have modified the traditional logopaedic diagnostics using variants of examination schemes and didactic material from well-known techniques. Diagnostic examination is divided into three stages: preparation, the basis and data analysis. The main stage included three blocks: the examination of sensorimotor, cognitive development and emotional-volitional sphere, the development of oral and written speech. The results of the diagnostics showed that the indicators of emotional-volitional sphere are lower in children of the experimental group than in children of the comparative group. Correction of activity (motive, programming, regulation, communication skills of writing) is allocated in an independent section of logopaedic work, using the method of neurolinguistics programming as a means of psychological correction, personal development, improving the effectiveness of correctional and pedagogical influence. Keywords: neuropsychological approach, diagnostics, general speech underdevelopment, neurolinguistics programming